Model Penguatan Kapasitas Pemerintah Desa dalam Menjalankan Fungsi Pemerintahan Berbasis Electronic Government (E-Government) menuju Pembangunan Desa Berdaya Saing - Sulismadi, Sulismadi; Wahyudi, Wahyudi; Muslimin, Muslimin (Universitas Muhammadiyah Ponorogo, 2017)
One aspect that needs to be studied more deeply about the village administration in the era of village autonomy is the ability of the human resources in the management of village government in accordance village governance objectives and the demands of, “Undang – undang no 06 Tahun 2014 about the village. The capacity of the village government deemed not qualified to run the authority possessed by law the village. Weak capacity of rural government impact on law implementation failure that led to the poor rural village development. This study examines these issues. This study used qualitative research methods. The unit of analysis of this research that the village government Landungsari Dau District of Malang, East Java. This study was conducted over three years (2016, 2017, 2018). The findings of the research during the last four months in the first year of the study is Landungsari village administration showed a good performance in governance at the village of village autonomy era (the era of the Village Law. The village government is able to carry out rural development planning, village administrative governance, and the financial management of the village properly. Nevertheless, the village government also faces serious problems is the lack of human resource capacity of the village administration, village very less quantity, and village officials do not understand the duties of each. To address these issues, the village government seeks to organize village governance based on information technology (e-government), but the effort has not worked well because the village government does not have a human resources professional in the field of information technology and the village government does not have enough budget to develop the e-government program. Therefore, the research team conducting FGD on the development of e-government program. FGD village government resulted in an agreement in cooperation with governmental science labs and e-government program APBDes budgeted in fiscal year 2017. Step next phase is the research team conducting FGD Phase II to design e-government as a means of governance villages effective and efficient, to disseminate the e-government, and publishes scientific articles on the model of governance based rural e-government in the Journal of Politics and Government Muhammadiyah University of Yogyakarta. Our advice as a researcher is a village government should make regulations governing Internet-based mechanism of public services (e-government). The regulation is to encourage villagers Landungsari to get used to using services based on the Internet, the district government of Malang should provide support to the village government to make innovations in governance, and the central government should support the village government to strengthen rural government institutions such as the addition of the village